A comparative study of psoriasis and psoriasiform lesion on basis of CD4 and CD8 cell infiltration - Safia Rana; Jairajpuri Shamim Zeeba; Jetley Sujata; Kudesia Madhur (Our Dermatology Online, 2012)
Introduction: Psoriasis is a chronic inflammatory skin disorder with immunological factors playing an important role in its pathogenesis. It is now regarded as a T cell mediated disorder in which lymphocytic infiltrates, mainly CD4 and CD 8 cells which provide a major contribution in the initiation and maintenance of psoriatic lesions.Methods: Skin biopsies from both psoriatic and psoriasiform lesions were stained with monoclonal antibodies against CD4 and CD8 and their percentage was calculated in the epidermis, upper dermis and lower dermis.Results: The difference of mean value of percentage of CD4 cells, among psoriasis and psoriasiform lesion in the epidermis was statistically insignificant(p=0.228), while it was significant in the upper dermis (p=0.002) and in lower dermis (p=0.043). The difference in the value of percentage of CD 8 cells was statistically significant in the epidermis(p=0.007), upper dermis (p=0.005), and the lower dermis (p=0.043)Conclusion: Both CD4 and CD 8 T cells are present in the appropriate anatomic locations to sustain lesional skin pathology in psoriasis and psoriasiform lesions.